Analisis Komunikasi Visual Pada Poster Sebagai Media Komunikasi Mendorong Jarak Sosial Di Jakarta Saat Epidemi Covid 19 - Arsa Widitiarsa Utoyo (LUGAS Jurnal Komunikasi, 2020)
Health campaigns about the covid 19 epidemic need to underlined as important actions to prevent viruses that cause fever, coughing, shortness of breath, chest pain and death. The health ministry and the local government need to move public awareness about healthy lifestyle. This research has analysed the key elements of health campaign posters in Jakarta. The Poster is still an active platform to tell data, schedules, display information, to persuade citizen in Jakarta. This study uses a qualitative approach, and uses case studies to visual analysis of local content and national poster design in Jakarta. The results show that local and national poster designs have different elements of the design, and it affects different posters. The results show that local and national poster designs have different colour, font, title, blank space, size and visual aids of the design results that affect different posters.